(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
Some of coordination chemical properties of carbacylamidophsphate (CAPh) type ligands - P, N-substituted structural analogues of β-diketones- are presented. It has been shown, that unsaturated d- and f-metals complexes of the composition ML or ML, (were M- d- or f-metal ion, L-CAPh ligand in deprotonated form) may be used as building blocks for the synthesis of bi-, tetra- and polynuclear compounds.